(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This study investigates the development of 6-7-year-old children’s understanding of elementary mathematics through an electronic platform based on interactive intelligence. The research explores how interactive intelligence within the electronic platform enhances children’s engagement and learning outcomes in math. By analyzing the effectiveness of interactive math games tailored to this age group, the study aims to contribute to our understanding of how technology can support mathematical education in early childhood.